REQUIEM VIR DIE TENK: AD INITIO AD FINEM - Nöthling, C.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
Affective statistics are frequently employed to support arguments for and against the continued operational deployment of the tank on the modern battlefield. In statistical evaluations, which of necessity sometimes are based on inferential techniques, military analysts tend to disregard the influence of such variables as technology. Any ’statistical’ projections as to the feasibility of tracked armour with main armament should not only take recent conflicts into account but must in fact be founded on a far broader, historically comparative basis of reference. On this premise the operational deployment of the tank is reviewed, with attention given to such determining factors as availability (with production as initial factor), use and losses during WWI, the intermediate years (1919 - 1939), WW II and the post-war period (1945 - 1980). The general conclusion at which the author arrives is that quantative factors playa decisive role in the course and outcome of conflicts in spite of the relative importance of doctrines, battle skill and tactics. However, quantitive considerations and resolutions have also lead to certain misconceptions as to the role of armour in modern warfare. In this respect acolytes of the tank tend to disregard the decisive role of air superiority. At the same time it appears that new developments in the field of manufacture are inadequate to counter the onslaught of fiscal considerations and the growing arsenal of antitank weapons.